2022
DOI: 10.1007/s00338-022-02300-4
|View full text |Cite
|
Sign up to set email alerts
|

Cross-generational heritability analysis of physiological traits in Porites astreoides across an inshore-offshore gradient in the Lower Florida Keys

Abstract: Estimating the heritable genetic variation in fitness-related traits is key to projecting the adaptive evolution of organisms in response to a changing environment. While heritability studies on reef-building corals to date support adaptive capacity, little is known about the dynamics of trait heritability across life stages in which distinct selective pressures can have long-lasting effects both within and across generations. In this study, we obtained heritability estimates for energetic and thermal stress r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…Two thermal stress experiments were conducted at the Key Largo Marine Research Laboratory in 2019 after mature swimming larvae were observed in all cultures (In × In, Off × Off, putative hybrid cross), which occurred on day 3 post‐fertilization: an acute stress at 36°C and a moderate stress at 32°C following Zhang et al (2022). For each experiment, six replicate 6 L polycarbonate larval bins (Vigors) were filled with 0.2 μm FSW and placed into a set of two shallow 32 L polycarbonate (Rubbermaid) water baths for temperature control ( n = 3 larval bins per bath).…”
Section: Methodsmentioning
confidence: 99%
“…Two thermal stress experiments were conducted at the Key Largo Marine Research Laboratory in 2019 after mature swimming larvae were observed in all cultures (In × In, Off × Off, putative hybrid cross), which occurred on day 3 post‐fertilization: an acute stress at 36°C and a moderate stress at 32°C following Zhang et al (2022). For each experiment, six replicate 6 L polycarbonate larval bins (Vigors) were filled with 0.2 μm FSW and placed into a set of two shallow 32 L polycarbonate (Rubbermaid) water baths for temperature control ( n = 3 larval bins per bath).…”
Section: Methodsmentioning
confidence: 99%
“…Two thermal stress experiments were conducted at the Key Largo Marine Research Laboratory in 2019 after mature swimming larvae were observed in all cultures (CRxCR, HRxHR, putative hybrid cross), which occurred on day 3 post fertilization: an acute stress at 36 °C and a moderate stress at 32 °C following (Zhang et al, 2022). For each experiment, six replicate 6 L polycarbonate larval bins (Vigors) were filled with 0.2 μm FSW and placed into a set of two shallow 32 L polycarbonate (Rubbermaid) water baths for temperature control (n = 3 larval bins per bath).…”
Section: Thermal Stress Challengesmentioning
confidence: 99%